Investigation of the exceptional charge performance of the 0.93Li4−xMn2O5–0.07Li2O composite cathode for Li-ion batteries. Issue 12 (9th March 2018) - Freire, M.; Diaz-Lopez, M.; Bordet, P.; Colin, C. V.; Lebedev, O. I.; Kosova, N. V.; Jordy, C.; Chateigner, D.; Chuvilin, A. L.; Maignan, A.; Pralong, V.
Abstract : Herein, we report a detailed study on the high-energy density nanostructured Li4− x Mn2 O5 –Li2 O composite with a high discharge capacity of 355 mA h g −1, constituting the highest value reported to date for a lithium–manganese oxide electrode. Abstract : Herein, we report a detailed study on the high-energy density nanostructured Li4− x Mn2 O5 –Li2 O composite with a high discharge capacity of 355 mA h g −1, constituting the highest value reported to date for a lithium–manganese oxide electrode. Its high capacity was previously wrongly attributed to the participation of Li4− x Mn2 O5 (Li4) alone. However, more detailed compositional, structural, and electrochemical analyses revealed the important role played by Li2 O during battery cycling that was able to increase the original capacity of Li4 by 100 mA h g −1 . The participation of Li2 O is evident during the first charge when it is mixed on the nanoscale with lithiated manganese oxide. The fully delithiated phase Li0 is formed after the first charge. Our structural study combining neutron and synchrotron diffraction and transmission electron microscopy demonstrates that lithium exchange essentially implies breathing of the average cubic framework accompanied by small local atomic rearrangements that mainly involve oxygen anions.